Chronotherapy of maxacalcitol on skin inflammation induced by topical 12-O-tetradecanoylphorbol-13-acetate in mice. (2nd September 2018) - Yoshioka, Daisuke; Ando, Hitoshi; Ushijima, Kentaro; Kumazaki, Masafumi; Fujimura, Akio
ABSTRACT: In general, chronotherapy is desirable for a more effective and/or safe dosage regimen. In this study, a daily rhythm of skin vitamin D receptor (VDR) and chronotherapeutic profiles of maxacalcitol, a vitamin D analogue, were evaluated using mice with skin inflammation induced by topical 12- O -tetradecanoylphorbol-13-acetate (TPA). This study showed that skin nuclear VDR expression in TPA-treated mice has a daily rhythm with the peak at the middle of active period. The effects of maxacalcitol were greater after dosing during early to middle of active period than those after dosing during early to middle of inactive period. These data suggest that chronotherapeutic profiles of maxacalcitol partly depend on the daily rhythm of skin nuclear VDR in TPA-treated mice. Because TPA-treated mice are considered as one of animal models of psoriasis, these animal data might be helpful for establishing chronotherapeutic approach of maxacalcitol in clinical practice.